Disparitas Kematian Maternal di Indonesia: Studi Ekologi dengan Analisis Spasial - Nurrizka, Rahmah Hida; Wahyono, Tri Yunis Miko (Media Kesehatan Masyarakat Indonesia, 2018)
This study is an analyze disparity of maternal mortality in Indonesia with spatial analysis using intermediate factor such as maternal health service, reproduction status, socio economic and demography. This study aimed to spatially analyze disparity of maternal mortality, analyze the influence and risk of maternal mortality on intermediate factors, and provide recommendations on maternal health problems in Indonesia. This study using ecological study design (agrerat studies), spatial analysis, bivariate analysis, and multivariate analysis. Unit of analysis in this study is districts/cities in Indonesia. The results showed that disparity of maternal mortality caused by intermediate factor gap between districts/cities in Indonesia, with the highest risk of maternal mortality occurred in eastern Indonesia. The dominant variables related to maternal mortality, namely population density with OR:0,283 (95% CI:0,185-0,430) and childbirth by skilled health personal with OR:1,745 (95% CI:1,081-2,815). The high risk of maternal mortality occurred in districts/cities with low coverage of fourth pregnancy (K4), low birth attendance (PN) coverage, low postpartum (KF) coverage, average number of children, low average education, and high poverty